Towards acceptance criteria for a digital euro - Nicolai Krüger; Jan Busche (IU Internationale Hochschule, 2023)
Alongside other central banks, the European Central Bank (ECB) is currently exploring the potential of a Central Bank Digital Currency (CBDC). Such a significant payment innovation requires compliance with the ECB's mandate based on the Treaties of the European Union, in addition to socio-technical and socioeconomic considerations. Thus, Information Systems (IS) researchers might witness and actively participate in one of the most important changes associated to currency-related fundamental rights in our time in the euro area. IS research can provide useful insights into technology acceptance criteria of a CBDC, which is a novel and unfamiliar technology for most people, and help identify requirements. Our paper provides an overview of the current state of development. Furthermore, we present a Technology Acceptance Model - based vignette study (N = 207) and derive design principles for a prospective digital euro (PDE). The results of the study show that acceptance by the German population can be assumed. However, there are significant differences depending on the final design choices.
Keywords: 004; Central Bank Digital Currency; European Central Bank; Digital Euro; Technology Acceptance Model; Intention to use; Cryptocurrencies